SARS-CoV-2 Antibody Response to the BNT162b2 mRNA Vaccine in Persons with Past Natural Infection - Kang, Yu Min; Choe, Kang-Won; Lee, Ki-Deok; Kim, Kwang Nam; Kim, Moon Jung; Lim, Jaegyun (Journal of Korean medical science, 2021)
There are still no agreed guidelines on the vaccination of coronavirus disease 2019 (COVID-19) for previously infected patients. Here, we present two seropositive healthcare workers (HCWs) working in an isolation ward who recovered from COVID-19 in April 2020 and got vaccinated with BNT162b2 vaccine in March 2021. We have assessed the clinical course, vaccine-related adverse events, and antibody response after natural infection and after first and second dose vaccination. One of the two HCWs was asymptomatic during quarantine, but the other had mild upper respiratory infection symptoms 1 day before admission, and the symptoms continued for 9 days. There was no pneumonic infiltration in chest X-ray in both patients, and no COVID-19 specific treatment was administered. Total immunoglobulin antibody and neutralizing antibody to anti-spike protein receptor-binding domain of severe acute respiratory syndrome coronavirus 2 were confirmed to be present in both HCWs in blood tests performed at 2 weeks and 4 weeks after discharge. Antibody response to mRNA vaccination showed marked elevation after the first vaccination, which was 30-40 times higher than that of antibody titer after natural infection in each patient (83.2 U/mL vs. > 2,500 U/mL in patient 1; 61.6 U/mL vs. > 2,500 U/mL in patient 2). Signal inhibition rate of neutralizing antibodies was also increased to over 97%. Due to this increased effect, there was little difference in antibody levels after the first and second dose. Both patients 1 and 2 suffered more from adverse vaccine reactions after the second vaccination than from COVID-19 symptoms.There are still no agreed guidelines on the vaccination of coronavirus disease 2019 (COVID-19) for previously infected patients. Here, we present two seropositive healthcare workers (HCWs) working in an isolation ward who recovered from COVID-19 in April 2020 and got vaccinated with BNT162b2 vaccine in March 2021. We have assessed the clinical course, vaccine-related adverse events, and antibody response after natural infection and after first and second dose vaccination. One of the two HCWs was asymptomatic during quarantine, but the other had mild upper respiratory infection symptoms 1 day before admission, and the symptoms continued for 9 days. There was no pneumonic infiltration in chest X-ray in both patients, and no COVID-19 specific treatment was administered. Total immunoglobulin antibody and neutralizing antibody to anti-spike protein receptor-binding domain of severe acute respiratory syndrome coronavirus 2 were confirmed to be present in both HCWs in blood tests performed at 2 weeks and 4 weeks after discharge. Antibody response to mRNA vaccination showed marked elevation after the first vaccination, which was 30-40 times higher than that of antibody titer after natural infection in each patient (83.2 U/mL vs. > 2,500 U/mL in patient 1; 61.6 U/mL vs. > 2,500 U/mL in patient 2). Signal inhibition rate of neutralizing antibodies was also increased to over 97%. Due to this increased effect, there was little difference in antibody levels after the first and second dose. Both patients 1 and 2 suffered more from adverse vaccine reactions after the second vaccination than from COVID-19 symptoms.